Identifying Optimal Program Models and Clinical Tools for Follow-Up Care. Issue 57 (3rd September 2021) - Gilmore, Katherine R; Rodriguez, M Alma
Abstract: Fifteen years ago, the Institute of Medicine (IOM) issued a report that defined Survivorship Care as a distinct phase of the cancer care continuum. The required domains to meet the health needs of cancer survivors were outlined in the report: cancer surveillance and screening, cancer prevention and lifestyle counseling, management of treatment related persistent or late effects, coordination of care, and psychosocial support services. In response to that report, The University of Texas MD Anderson Cancer Center implemented a tiered survivorship care model that is risk based. The core principle is that cancer survivors' health needs will depend on the cancer treatment and disease-specific risks. We here describe this model for low-, intermediate-, and high-risk cancer survivors, in which comanagement between oncology and primary care providers is risk dependent. Our clinical model defines transition as appropriate when there is a minimal risk of primary cancer relapse, which is specific to each cancer type and disease stage. This model is embedded into disease-specific clinical practice algorithms, aligned with the IOM domains of care. Over the past 10 years, we have successfully transitioned nearly 25 000 patients to disease-specific survivorship clinics, providing care based on the IOM domains. We have learned from our process that expansion of survivorship care into established clinical settings requires engagement of champions and key clinical stakeholders. Future directions for survivorship care should explore the application and potential benefits of telemedicine as a care delivery system to meet the needs of cancer survivors.